Learning and Teaching Historical Content in Primary Education - Letina, Alena; Kegel, Lucija (Revija za elementarno izobraževanje, 2024)
This paper presents the results of a study whose primary goal was to determine the level of future teachers’ knowledge of historical content taught in primary school, the ways they self-assess their abilities to organize the learning and teaching of historical content, and their beliefs about the possibilities of teaching history in primary education. The research was conducted using a survey of 157 fourth- and fifth-year students in teacher education programs. The results indicate that students demonstrate a satisfactory level of knowledge about historical content taught in primary education. They self-assess their skills for teaching of historical content as mostly developed and have positive beliefs about the possibilities of teaching and learning history at the primary education level.